THE EFFECTS OF DIFFERENT SHAPED BAFFLE BLOCKS ON THE ENERGY DISSIPATION - Al-Mansori, Nassrin Jassim Hussien; Alfatlawi, Thair Jabbar Mizhir; Hashim, Khalid S.; Al-Zubaidi, Laith S. (Salehan Institute of Higher Education, 2020)
Stilling basins can be defined as energy dissipaters constructed of the irrigation systems. This study aims at investigating the performance of the new seven baffle blocks design in terms of reducing the dimensions of stilling basins in irrigation systems. In order to assess the hydraulic efficiency of a new model for baffle block used in stilling basins, a Naval Research Laboratory (NRL) has conducted. The results of this study demonstrate that the performance of the new baffle block, in term of hydraulic jump length reduction and hydraulic energy dissipation, it's better than standard blocks. However, the ratios of the drag resistance attributed to the new baffles block (FB / F2) have been larger than that applied on the normal block. It was found that the new block dissipates the energy by 9.31% more than the concrete block, and decreases the length of the hydraulic jump by 38.6% in comparison with the standard blocks. However, the new block maximizes the drag force ratio by 98.6% in comparison with the standard baffle blocks. The findings indicated that in terms of energy reduction and dissipation in the length of the hydraulic jump, the new block is superior to the other kinds.